2021
DOI: 10.3390/agriculture11100939
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage on the Mollisols Physicochemical Properties, Seed Emergence and Yield of Maize in Northeast China

Abstract: Tillage practices are critical for sustaining soil quality necessary for successful crop growth and productivity, but there are only few studies for strip tillage (ST) in the Mollisols region of Northeast China at present. A long-term (≥10-year) study was carried out to investigate the influence of within the tilled row (IR) and between rows (BR) in ST (10-year), conventional tillage (CT, 14-year) and no tillage (NT, 14-year) treatments on soil physicochemical properties. Soil samples were taken in May of 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…These results showed that the conversion of natural grassland/forest to farmland reduced soil quality and increased soil erodibility because of more frequent soil disturbances and less vegetation coverage, plant community diversity and root density (Manzoni & Porporato, 2009; Mohammad & Adam, 2010; Vityakon, 2007). In a similar study area, Chen, Zhang, et al (2021) reported that soil loss decreased rapidly during the first 3 years of revegetation and then decreased slowly, with a stable loss rate after 15 years. The benefits of revegetation can be attributed to the following: (1) the plants stems, leaves and litter intercept raindrops and reduce runoff flow velocity; (2) vegetation strengthens the binding action of plant roots and improves soil infiltration capacity, resulting in less soil erosion than in the BL treatment (Garcia‐Estringana et al, 2010; Liu et al, 2018; Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…These results showed that the conversion of natural grassland/forest to farmland reduced soil quality and increased soil erodibility because of more frequent soil disturbances and less vegetation coverage, plant community diversity and root density (Manzoni & Porporato, 2009; Mohammad & Adam, 2010; Vityakon, 2007). In a similar study area, Chen, Zhang, et al (2021) reported that soil loss decreased rapidly during the first 3 years of revegetation and then decreased slowly, with a stable loss rate after 15 years. The benefits of revegetation can be attributed to the following: (1) the plants stems, leaves and litter intercept raindrops and reduce runoff flow velocity; (2) vegetation strengthens the binding action of plant roots and improves soil infiltration capacity, resulting in less soil erosion than in the BL treatment (Garcia‐Estringana et al, 2010; Liu et al, 2018; Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…These results showed that the conversion of natural grassland/forest to farmland reduced soil quality and increased soil erodibility because of more frequent soil disturbances and less vegetation coverage, plant community diversity and root density (Manzoni & Porporato, 2009;Mohammad & Adam, 2010;Vityakon, 2007). In a similar study area, Chen, Zhang, et al (2021) reported that soil loss decreased rapidly during the first 3 years of Liu et al, 2018;Zhang et al, 2010). Revegetation is critical to reducing soil erosion and improving soil nutrient retention (Guo et al, 2020;Ran et al, 2013;Wen et al, 2019;Yan, Xue, et al, 2021;Zheng, 2006).…”
Section: Tn and Tp Loss In Sedimentmentioning
confidence: 84%
See 3 more Smart Citations